2018
DOI: 10.1038/s41598-018-33044-3
|View full text |Cite
|
Sign up to set email alerts
|

Bridging of membrane surfaces by annexin A2

Abstract: The protein-mediated formation of membrane contacts is a crucial event in many cellular processes ranging from the establishment of organelle contacts to the docking of vesicles to a target membrane. Annexins are Ca2+ regulated membrane-binding proteins implicated in providing such membrane contacts; however, the molecular basis of membrane bridging by annexins is not fully understood. We addressed this central question using annexin A2 (AnxA2) that functions in secretory vesicle exocytosis possibly by providi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 42 publications
0
32
0
Order By: Relevance
“…Altered calcium homeostasis has been observed within breast cancer, however, it is currently unclear whether the dysregulation of calcium binding proteins like Annexin A2 are a cause or a consequence of this imbalance [64]. Despite this, it is known that Ca 2+ level within the cell regulates Annexin A2 s affinity for its binding partners and cellular components such as the plasma membrane and the actin cytoskeleton [51,66,67]. Apart from Annexin A2, calcium binding proteins such as the S100 family (several of which were identified in our screen, Table S1) have been thoroughly investigated in the context of cancer, as reviewed by Bresnick et al [68] and these, along with Annexin A2, have the potential to be utilized as prognostic or therapeutic targets in breast cancer [69].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Altered calcium homeostasis has been observed within breast cancer, however, it is currently unclear whether the dysregulation of calcium binding proteins like Annexin A2 are a cause or a consequence of this imbalance [64]. Despite this, it is known that Ca 2+ level within the cell regulates Annexin A2 s affinity for its binding partners and cellular components such as the plasma membrane and the actin cytoskeleton [51,66,67]. Apart from Annexin A2, calcium binding proteins such as the S100 family (several of which were identified in our screen, Table S1) have been thoroughly investigated in the context of cancer, as reviewed by Bresnick et al [68] and these, along with Annexin A2, have the potential to be utilized as prognostic or therapeutic targets in breast cancer [69].…”
Section: Discussionmentioning
confidence: 99%
“…We thus tested the value of our experimental design by conducting a focused study on Annexin A2-a protein identified in both our migration and invasion experiments. Annexin A2 is a calcium ion regulated membrane binding protein [67] found to play a role in a wide range of cellular processes, from endo-and exo-cytosis to proliferation and apoptosis [51]. One of its best-known functions is its hand in the proteolytic cascade, triggered by the activation of plasmin.…”
Section: Discussionmentioning
confidence: 99%
“…Annexin 2 is a protein that is part of the lipid rafts in the intestinal brush border and is associated with actin filaments mediating in membrane-membrane and membranecytoskeletal interactions influencing actin cytoskeletal remodeling through targeting signaling molecules to membrane domains. As a consequence it plays an important role in membrane trafficking and stabilization of membrane-associated protein complexes with the actin cytoskeleton and has been implicated in the migration of various cell types including epithelial cells and cell matrix interaction [41,49]. Moreover, annexin 2 has been shown to induce clustering of specific plasma membrane phospholipids and play a role in lipid domain formation [41].…”
Section: Discussionmentioning
confidence: 99%
“…Annexin 2 is a protein that is part of the lipid rafts in the intestinal brush border and is associated with actin filaments mediating in membrane-membrane and membrane-cytoskeletal interactions influencing actin cytoskeletal remodeling through targeting signaling molecules to membrane domains. As a consequence, it plays a crucial role in membrane trafficking and stabilization of membrane-associated protein complexes with the actin cytoskeleton and has been involved in the migration of several types of cells, such as epithelial cells and cell matrix interaction [41,[49][50][51]. Moreover, annexin 2 induces clustering of specific plasma membrane phospholipids and is involved in lipid domain formation [41].…”
Section: Discussionmentioning
confidence: 99%